Шивээнгол бүрдлийн геохими, геохронологийн шинэлэг үр дүнгээс - Т.Оюунчимэг; Ц.Наранцэцэг; Х.Удаанжаргал; Б.Энхдалай; Ж.Энхтуяа; Б.Үржинханд (Geological Issues, 2025)
The paper presents the latest geochronological and geochemical results on alkali granites of the Shiveengol complex, a Mesozoic alkali granitoid found of the Lake Fold System, in Western Mongolia. The granitoids are characterized by geochemical enrichment in large-ion lithophile elements (LILE) such as Rb, Nd, Th and U, and depletion in high-field strength elements (HFSE) such as Sr, Zr and Ti. Geochemically, it reveals similarities with A-type granites formed within plate settings. U–Pb dating results show that the absolute age of the syenite is 210.6±2.4 Ma, which is Late Triassic.